The Impact of Decision Support Systems on Organizational Innovation: Field Study in Industrial Companies in Dhofar Governorate - Tawfik, Omar Ikbal; Bilal, Zaroug Osman; Kshoub, Salem Bakhit (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of the research is to identify the impact of decision support systems on organizational creativity in industrial companies in Dhofar Governorate. The research relied on the questionnaire in collecting information. The research population consisted of employees in the top and middle management of three industrial companies in Dhofar Governorate (Raysut Cement, Dhofar Energy, and Salalah Methanol Company) and they (97) employees. Questionnaires were distributed to all members of the study community in the three companies, and the researcher retrieved (93) a valid questionnaire for statistical analysis. The researcher used the descriptive analytical method in collecting data, analyzing it, answering research questions and testing their hypotheses. The most important results of the research: the presence of a statistically significant effect to support senior management and the type of support systems used on organizational creativity at the level of statistical significance (0.05) Dhofar Governorate industrial companies. And the absence of a statistically significant effect of the available capabilities of decision support systems on organizational creativity at the level of statistical significance (0.05). Among the most important recommendations: Raising the levels of creativity of workers in industrial companies through holding workshops and developing them to the best practical practices in the field of benefiting from the outputs of decision support systems. And enhancing the inputs of decision support systems in industrial companies to make new and modern contributions to the decision-making process.